2008
DOI: 10.1080/02673030802416619
|View full text |Cite
|
Sign up to set email alerts
|

Same Neighbourhood … Different Views? A Confrontation of Internal and External Neighbourhood Reputations

Abstract: Abstract. Residents and non-residents are likely to think differently about a neighbourhood's reputation. Relatively little is known about the similarities and differences between these internal and external types of neighbourhood reputation or the relationship between reputations and 'real' or 'objective' neighbourhood characteristics. This paper addresses two points: first, the extent to which neighbourhood reputations differ between and within groups; second, the extent to which these neighbourhood reputati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 52 publications
2
63
0
Order By: Relevance
“…they agreed with the statement: 'Many people in Glasgow think this neighbourhood has a bad reputation'-this is akin to what has been called the 'selfreflecting image', the image that residents believe is held by outsiders (Skifter-Andersen, 2008). Research has indicated that residents' assessments of the reputations of their neighbourhoods (the so-called 'internal image') are typically more positive than that held by outsiders (the so-called 'external image') (Permentier et al, 2008). Second, it was found that only a relatively small number of residents in the inner city estates, c. 35 per cent, derived status-related psychosocial benefits from where they lived, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…they agreed with the statement: 'Many people in Glasgow think this neighbourhood has a bad reputation'-this is akin to what has been called the 'selfreflecting image', the image that residents believe is held by outsiders (Skifter-Andersen, 2008). Research has indicated that residents' assessments of the reputations of their neighbourhoods (the so-called 'internal image') are typically more positive than that held by outsiders (the so-called 'external image') (Permentier et al, 2008). Second, it was found that only a relatively small number of residents in the inner city estates, c. 35 per cent, derived status-related psychosocial benefits from where they lived, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of neighbourhood characteristics associated with a perceived negative external reputation among residents (e.g. Permentier et al, 2008) are not the same thing, since this only tells us what influences residents' perceptions, not how beliefs are formed and transmitted, and what the actual nature of those external beliefs is.…”
Section: Reputation Studies In Recent Neighbourhoods Researchmentioning
confidence: 99%
“…First, ethnic groups differ in their assessment of different neighbourhoods as people tend to have a preference for neighbourhoods where the ethnic and socioeconomic characteristics of the majority of the population are similar to their own (Permentier et al, 2008). Neighbourhoods differ in the extent to which they offer their inhabitants the resources and facilities to meet and mingle (Tolsma et al, 2009), and natives, in particular, may receive and exploit these resources and facilities in a more advantageous manner than immigrants.…”
Section: For Whom Do Geographical Effects Matter?mentioning
confidence: 99%
“…This probably relates to the fact that natives differ in their assessment of neighbourhoods compared with immigrants. People generally tend to have a preference for neighbourhoods where the ethnic and socioeconomic characteristics of the majority of the population are similar to their own (Permentier et al, 2008), but our result suggests that ethnic minorities may have a stronger preference for neighbourhoods where the ethnic and socioeconomic characteristics of the majority of the population are similar to their own than do natives and also neighbourhoods with a high ethnic concentration and low economic development may hinder Dutch local social integration, as native Dutch people might feel threatened by the high concentration of ethnic minorities. Overall, our results fail to reject hypothesis 3.…”
Section: For Whom Do Geographical Effects Matter?mentioning
confidence: 99%
“…Based on their evidence from Utrecht, fourth largest city in the Netherlands, and one with substantial socio-spatial exclusion problems, Permentier, Van Ham and Bolt [25] conclude that the socioeconomic and ethnic mixture determines the reputation of a neighbourhood, which in turn affects its ability to attract the 'right type' of new residents.…”
Section: Market-based and Socio-demographic Effectsmentioning
confidence: 99%